Spektrum Frekuensi Sinyal EEG Terhadap Pergerakan Motorik dan Imajinasi Pergerakan Motorik - Endro Yulianto (Faculty of Engineering, Universitas Gadjah Mada, 2013)
This research is aimed to getji-equency spectrum of EEG signals for the motor movement and imagination of motor movement. EEG data is measured from scalp electrode of C3, C4, P3 and P4 (Central and Parietal). The motor movement in this research is